Molecular characterization of pathogenicity locus (PaLoc) and tcdC genetic diversity among tcdA+B+Clostridioides difficile clinical isolates in Tehran, Iran - Kodori, Mansoor; Ghalavand, Zohreh; Yadegar, Abbas; Eslami, Gita; Azimirad, Masoumeh; Krutova, Marcela; Abadi, Alireza; Zali, Mohammad Reza (Anaerobe, 2020)
Clostridioides difficile is the main cause of healthcare-associated diarrhea worldwide. It is proposed that certain C. difficile toxinotypes with distinct pathogenicity locus (PaLoc) variants are associated with disease severity and outcomes. Additionally, few studies have described the common C. difficile toxinotypes, and also little is known about the tcdC variants in Iranian isolates. We characterized the toxinotypes and the tcdC genotypes from a collection of Iranian clinical C. difficile tcdA+B+ isolates with known ribotypes (RTs). Fifty C. difficile isolates with known RTs and carrying the tcdA and tcdB toxin genes were analyzed. Toxinotyping was carried out based on a PCR-RFLP analysis of a 19.6 kb region encompassing the PaLoc. Genetic diversity of the tcdC gene was determined by the sequencing of the gene. Of the 50 C. difficile isolates investigated, five distinct toxinotypes were recognized. Toxinotypes 0 (33/50, 66%) and V (11/50, 22%) were the most frequently found. C. difficile isolates of the toxinotype 0 mostly belonged to RT 001 (12/33, 36.4%), whereas toxinotype V consisted of RT 126 (9/11, 81.8%). The tcdC sequencing showed six variants (35/50, 70%); tcdC-sc3 (24%), tcdC-A (22%), tcdC-sc9 (18%), tcdC-B (2%), tcdC-sc14 (2%), and tcdC-sc15 (2%). The remaining isolates were wild-types (15/50, 30%) in the tcdC gene. The present study demonstrates that the majority of clinical tcdA+B+ isolates of C. difficile frequently harbor tcdC genetic variants. We also found that the RT 001/toxinotype 0 and the RT 126/toxinotype V are the most common types among Iranian isolates. Further studies are needed to investigate the putative association of various tcdC genotypes with CDI severity and its recurrence.
Keywords: Young Adult; Feces; represorové proteiny; polymerázová řetězová reakce; Male; Molecular Typing; Iran; Bacterial Proteins; genetická variace; mladý dospělý; Genotype; Clostridioides (clostridium) difficile; virulence; Adolescent; feces; Child; tcdA(+)B(+) isolates; dítě; Adult; Aged; dospělí; ribotypizace; Clostridioides difficile; senioři; mužské pohlaví; Clostridium Infections; tcdC; Virulence; Ribotype; klostridiové infekce; mladiství; senioři nad 80 let; DNA, Bacterial; DNA bakterií; lidé; ženské pohlaví; Humans; Ribotyping; bakteriální proteiny; Aged, 80 and over; Repressor Proteins; molekulární typizace; polymorfismus délky restrikčních fragmentů; Bacterial Toxins; genotyp; Polymerase Chain Reaction; Genetic Variation; Írán; Female; Toxinotype; lidé středního věku; PaLoc; Polymorphism, Restriction Fragment Length; Middle Aged; bakteriální toxiny